Preventive Patterns of Housewives in Preventing Anxiety as the Impact of Watching Television Movie - Nasution, Nurhasanah; Basit, Lutfi; Ginting, Rahmanita (Budapest International Research and Critics University, 2021)
During the COVID-19 pandemic, watching television is an alternative choice for entertainment at home. Because activities outside the home are limited. One of the entertainments that are requested by women is television films or soap operas completed in one run. The television film that has the highest rating is